Fundamentals of Machine Learning: Towards the Development of Intelligent Computational Models - Rizky A, Galih Prakoso (IHSA Institute, 2024)
This research examines the fundamental principles of machine learning (ML) and their significance in the development of intelligent computational models. By exploring core learning paradigms supervised, unsupervised, and reinforcement learning along with optimization strategies, model evaluation, and validation techniques, the study highlights how these elements collectively shape the effectiveness of ML applications. A review of existing literature over the past decade illustrates the rapid advancements in algorithms, architectures, and applications that have expanded the scope of computational intelligence across diverse domains such as healthcare, finance, and autonomous systems. The findings underscore that a clear understanding of ML fundamentals not only enhances real-world model performance but also provides a framework for guiding future research and innovation in intelligent systems. Despite these opportunities, the study also identifies challenges including data quality, interpretability, generalization, and ethical concerns, which must be addressed to ensure responsible and impactful implementation. Ultimately, this research concludes that the strength of intelligent computational models rests on their alignment with foundational ML principles, balancing technical progress with societal and ethical considerations.